LEVEL STRUCTURE OF VALUE-MEANING SELF-REGULATION OF THE PERSON - Pelekh, Vladyslav (Mountain School of Ukrainian Carpaty, 2024)
The concept of «life» of the individual is determined primarily by those values that constitute his/her personal core. At the same time, the unfolding of the essence occurs due to the activity of the individual, both at the conative level (life in itself), and at the cognitive level (a person’s prognostic reflection of the surrounding reality), as well as at the affective level (feelings). Amplification of the value-meaning self-regulation of the individual, mainly in the paradigm of the cognitive sphere, this is a kind of project of life, which in one way or another is realized by the person himself/herself or humanity as a whole. Such a life project can be developed to the maximum extent, that is, the entire future life of a person must be developed in order to realize values, goals and tasks. At the same time, such a project can be condensed in the paradigm of which important scripts of the person’s life can be actualized. The individual’s exit to the level of life design (a strategic level) is impossible without meta-reflection, which provides not only a holistic view of one’s own life, but also its understanding in the paradigm of historical time (of each individual person and of all humanity as a whole). In the same way, through value-semantic self-regulation of the personality, a person can reveal the content of his/her behavior (meanings, senses, processes of saving and processing information, systemic reflection, formulation of goals and planning of the activities), as well as actions (motives, direct reflection of the reality, emotions, objective reflections and operational level of regulation). In this regard, the scheme of the analysis of value-semantic self-regulation of the individual is quite understandable, because the analysis itself is related to the disclosure of the content of these concepts, their dialectic of the development and mutual transitions. However, the most important thing is that these concepts reveal life (behavior and behavioral actions, human activity), which, given the value-meaning self-regulation of the individual, are amplified taking into account the logics of the dynamic structure of a human psyche.